Disentangling autism spectrum and attention-deficit/hyperactivity symptoms over development in fragile X syndrome. (September 2020) - Doherty, Brianna Ruth; Longhi, Elena; Cole, Victoria; Karmiloff-Smith, Annette; Cornish, Kim; Scerif, Gaia
Highlights: Attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) symptoms relate longitudinally in fragile X syndrome. Correlations held over three time-points for ADHD symptoms and ASD symptoms. Structural equation modeling (SEM) showed that ADHD symptoms at time 2 predicted ASD symptoms at time 3. This result highlights the need to study outcomes longitudinally. Findings inform the comorbidity of the two symptom domains in FXS. Abstract: Even genetic disorders associated with monogenic aetiologies are characterized by complex and variable risk for poor outcomes, highlighting the need to follow trajectories longitudinally. Here, we investigated the longitudinal relationships between attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) symptoms in a population at high risk for both: boys with fragile X syndrome. 59 boys with fragile X syndrome aged 3–10 years old at entry participated in this study, and were followed up one and two years after their first visit. As expected, we found strong relationships over three timepoints for ADHD symptoms (as measured by the parent-rated Conners scale) and ASD symptoms (as measured by the Social Communication Questionnaire [SCQ]). In addition, using structural equation modeling (SEM) we found that ADHD symptoms at time 2 predicted ASD symptoms at time 3, suggestive of a causal relationship. Importantly, these relationships hold when including chronological age at entry to the study, as well as when including severity of impairment as measured by IQ, and their effects on both ASD and ADHD symptoms do not reach significance. This result highlights the need to study outcomes longitudinally and it informs the comorbidity of the two symptom domains in FXS as well as their potential directionality, both of which have been little researched. In addition, our findings may suggest a future need to study how ADHD symptoms and their treatment impact individuals with ASD.